Implementasi Teknik Kursi Kosong Terhadap Kecemasan Korban Bullying Di SMA Negeri 1 Darul Imarah Aceh Besar - Naqiatsyah, Genari; Muslima (Educator Development Journal, 2024)
Anxiety in victims of bullying arises because they feel that they are not perfect, and consider themselves weak so that they are unable to defend themselves who are the targets of repeated aggressive and manipulative treatment, both physically and mentally. Treatment to reduce the anxiety of victims of bullying, one of which is the empty chair technique through individual counseling because it can help the counselee to express all pent-up emotions and say what has been true that has not been able to be conveyed so that it can be said by means of students who are victims of bullying imagining the bully being present in front of them. This research aims to determine the implementation of the empty chair technique on the anxiety of bullying victims at SMA Negeri 1 Darul Imarah Aceh Besar. This quantitative research uses an experimental method with (One Group Pre-Test, Post-Test). The data collection technique used a Likert scale form with a population of 26 students from class The results of the research showed that the implementation of the empty chair technique significantly reduced the anxiety of bullying victims, as indicated by the change in the average score from the pre-test from 103.5 to 79.75 in the post-test. From the results of the hypothesis test, ttable < tcount = 2.353 < 23.041. From the comparison it was decided that Ho was rejected and Ha was accepted. Based on the research results, it was concluded that the implementation of the empty chair technique could reduce the anxiety of bullying victims at SMA Negeri 1 Darul Imarah Aceh Besar